COMPARISON OF DIFFERENT METHODS FOR EXPRESSION ANALYSIS ON THE EXAMPLE OF “CCHC-ZINC FINGER (ZF-CCHC)” GENE, REGULATING DROUGHT TOLERANCE IN CHICKPEA PLANTS (Cicer arietinum L.) - Khassanova, G.; Kuzbakova , M.; Jatayev , S.; Gabdola , A.; Oshergina , I.; Ten , E. (Eurasian Journal of Applied Biotechnology, 2023)
In this study, six zinc finger genes with CCHC domain (ZF-CCHC) were analyzed in chickpea plants under drought conditions in four accessions from Kazakhstan and International germplasm collections. In the result, three genes with high levels of expression were identified and analyzed: A3-1084, B-6505 and E-0714, as well as lower levels of the expression gene A2-6319 in response to drought in chickpea plants. Semi-quantitative and quantitative real-time PCR - two methods were assessed and compared for the expression analysis of isolated genes. A strong similarity was found between average values of expression, and with r = 0.91 correlation coefficient. The results obtained by two different methods showed a full consensus. However, only the quantitative real-time PCR is suitable for the analysis of gene expression levels in each genotype, while the semi-quantitative method is based on average values for all studied genotypes. Thus, based on an example chickpea, a high similarity between results of average gene expression rates in all studied genotypes was found in the analysis of four ZF-CCHC genes involved in plant response to drought. At the same time, the advantages of the quantitative real-time PCR method for gene expression analysis in each genotype are shown in the studied chickpea accessions. Two studied genes, A3-1084 and E-0714, were most promising for the analysis to produce new drought tolerant chickpea varieties. These genes had significantly increased expression levels in plants of cultivars Kamila 1255 and Louch with a high tolerance to drought.